Queens of mystery. [Series 1] [videorecording (DVD)] - Graham, Julie, 1965-; Redmond, Siobhan, 1959-; Woodward, Sarah; Vinall, Olivia (Acorn Media, 2019)
"The "wickedly offbeat" (Parade), contemporary mystery series follows the adventures of newly promoted Detective Sergeant Matilda Stone and her three crime-writing aunts as they solve murders in the picturesque English region of Wildemarsh. Though Matilda's strict boss warns her that homicides are police-only matters, her aunts can't help but offer their expertise, as well as unsolicited dating advice. As Matilda contends with a novelist killed during a blackout at an awards ceremony, an aging rock star strangled before her band's reunion tour, and an actor killed onstage, the one case she can't seem to crack is the unexplained disappearance of her mother more than 20 years ago."--Container.